Genetic complexity of the human surfactant-associated proteins SP-A1 and SP-A2 - Silveyra, Patricia (2012)
Pulmonary surfactant protein A (SP-A) plays a key role in innate lung host defense, in surfactant-related functions, and in parturition. In the course of evolution, the genetic complexity of SP-A has increased, particularly in the regulatory regions (i.e. promoter, untranslated regions). Although most species have a single SP-A gene, two genes encode SP-A in humans and primates (SFTPA1and SFTPA2). This may account for the multiple functions attributed to human SP-A, as well as the regulatory complexity of its expression by a relatively diverse set of protein and non-protein cellular factors. The interplay between enhancer cis-acting DNA sequences and trans-acting proteins that recognize these DNA elements is essential for gene regulation, primarily at the transcription initiation level. Furthermore, regulation at the mRNA level is essential to ensure proper physiological levels of SP-A under different conditions. To date, numerous studies have shown significant complexity of the regulation of SP-A expression at different levels, including transcription, splicing, mRNA decay, and translation. A number of trans-acting factors have also been described to play a role in the control of SP-A expression. The aim of this report is to describe the genetic complexity of the SFTPA1 and SFTPA2 genes, as well as to review regulatory mechanisms that control SP-A expression in humans and other animal species.